P-Chiral Phosphine Sulfide Synthesis by Combination of Enzymatic Desymmetrization and Successive Deformylative P–C Cross-Couplings - Ohta, Hidetoshi; Nakashima, Yoshiki; Kayahara, Kento; Hashimoto, Naoki; Tanaka, Ippei; Tadokoro, Tomoki; Watanabe, Yutaka; Hayashi, Minoru (Synlett, 2022)
A process for the synthesis of P-chiral triarylphosphine sulfides via sequential Pd-catalyzed stereospecific P–C coupling reactions of P-chiral precursors prepared by enzymatic desymmetrization was developed. Three independent aryl substituents could be introduced onto the P atom by the sequential P–C couplings under mild conditions while retaining the high enantiopurity.
Keywords: P-chiral phosphine; phosphine sulfide; P–C coupling; palladium; enzymatic desymmetrization